Semantyczne zagadnienia dzieła fiImowego. Przyczynek do teorii budowy postaci człowieka na ekraniew - EDWARD ŻEBROWSKI (Images)
Semantic issues of film. A contribution to the theory of creating the human character on the screen Edward Żebrowskiss masters thesis “Semantyczne zagadnienia dzieła filmowego. Przyczynek do teorii budowy postaci człowieka na ekranie” (“Semantic issues of film. Contribution to the theory of the creation of human character on screen”), which he defended in 1965, has not yet been published as a whole nor in any part. In his work, Żebrowski focuses on the issue of creating film characters, understood as part of the film material, deliberately omitting the aspect of acting. Using broad the- oretical contexts the author arrives at practical conclusions related to filmmaking